The four kinds of sales people : - Mache, Chuck (John Wiley & Sons, 2007)
During his two decades of selling, managing, building, and leading salespeople and companies in a variety of industries, Chuck Mache has learned that there are four distinct kinds of salespeople. Gleaned from his years in the trenches, The Four Kinds of Sales People is a business fable that exposes the traits and characteristics of these four types and outlines how and why salespeople excel–or don’t. The story follows four fictional salespeople, each of whom epitomizes the characteristics of a particular sales style, and provides a clear and exacting description of how each type goes about selling. Mache exposes the strengths and weaknesses of these salespeople and provides expert insight on what each type of salesperson requires to achieve next-level success. For salespeople, sales managers, and executives, this entertaining and practical book shows how to pinpoint personality traits and design a personalizedstrategy for unlimited sales success.